"Make your own religion": The fictive religion assignment as educational game. (19th October 2018) - Zeller, Benjamin E.
Abstract: This article considers the "create your own religion" or "fictive religion" assignment as a pedagogical tool, contextualizing it within the scholarship of teaching and learning, and positioning it as a tool for broad adoption in a variety of courses. I argue that we ought to conceptualize the fictive religion assignment as an instructional game, and make use of scholarship on teaching through games as a foundation for my analysis. While I offer the example of my own fictive religion assignment as a case study, the overall argument is a theoretical one, namely that the assignment works because of the nature of games.